1989
DOI: 10.1159/000185283
|View full text |Cite
|
Sign up to set email alerts
|

The Kallikrein-Kinin and Renin-Angiotensin Systems in Nephrotic Syndrome

Abstract: We previously found that virtually all patients with nephrotic syndrome (NS) excrete supranormal amounts of urinary kallikrein; it is known that activity of the renin-angiotensin system (RAS) is increased in some such patients. We therefore studied the relationship between urinary kallikrein excretion (UKa) and plasma renin activity (PRA) in 16 patients with NS. Compared with healthy controls, PRA was normal in 8 subjects and elevated in 8; UKa was elevated in the high-renin group (40.4 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Uri nary kallikrein excretion was inversely correlated with proteinuria and returned toward normal as proteinuria resolved. In contrast, Cumming et al [78] found an increase in urinary kallikrein excretion in nephrotic hu mans.…”
Section: Acels and The Renin-angiotensin And Kallikrein-kinin Systemsmentioning
confidence: 82%
“…Uri nary kallikrein excretion was inversely correlated with proteinuria and returned toward normal as proteinuria resolved. In contrast, Cumming et al [78] found an increase in urinary kallikrein excretion in nephrotic hu mans.…”
Section: Acels and The Renin-angiotensin And Kallikrein-kinin Systemsmentioning
confidence: 82%